AFEX pretreatment and enzymatic conversion of black locust (Robinia pseudoacacia L.) to soluble sugars - Garlock, Rebecca J. (2013)
Black locust (Robinia pseudoacacia L.), like willow and poplar, is a hardwood species which can be grown in coppice for bioenergy production, and because of its nitrogen-fixing ability, it can be cultivated with higher yields on less productive land. For these experiments, we examined the feasibility of using ammonia fiber expansion (AFEX) pretreatment to increase the saccharification yields from black locust grown for bioethanol production, as well as examine the impact of posttreatments (hot-water washing and additional size reduction) on sugar yields. The optimal AFEX conditions for black locust were 180°C, 1.0 g NH3/g dry biomass, 2.5 g H2O/g dry biomass, for 30 min residence time, and of the parameters tested, temperature had the greatest impact on yields. Yields from the sample without posttreatment and hydrolyzed at the standard enzyme loading were very low: <30% glucose and ∼50% hemicellulose. Both hot-water washing and size reduction improved yields; however, size reduction had a more significant effect indicating that increasing enzyme accessibility is more important for digestibility as opposed to the removal of soluble inhibitors. The effect of size reduction was comparable to that obtained by quadrupling the enzyme loading, increasing glucose yields by ∼20–30% and hemicellulose yields by ∼20%. Untreated black locust is known to contain compounds which are inhibitory to both enzymes and microorganisms and AFEX pretreatment neutralizes this inhibitory effect to some extent.